Women's resilience against politically driven digital violence and legal responses analysis in Indonesia - Puji Lestari; Aprila Niravita; Erisandi Arditama; Eta Yuni Lestari; Emmanuel Ofori Gyadu (Jurnal Civics: Media Kajian Kewarganegaraan, 2026)
Women’s responses to politically driven digital violence have become increasingly significant in Indonesia, where such threats undermine equal political participation. Despite the existence of legal frameworks governing elections, digital spaces, and gender-based violence, many remain legally inadequate and insufficiently responsive to women as victims of cyber violence. Existing studies tend to treat digital violence as a cybercrime issue or focus narrowly on women’s political participation, often neglecting its digital dimension. This study addresses that gap by conducting a comprehensive normative legal analysis within the broader framework of democracy and human rights. Using a normative legal research method and literature review, it examines the 1945 Constitution of the Republic of Indonesia, CEDAW, and relevant legal instruments, including Human Rights Law, Election Law, Electronic Information and Transactions Law, Law on Sexual Violence Crime, and regulations issued by the Ministry of Women Empowerment and Child Protection and the General Election Commission. The findings indicate that digital political violence against women commonly manifests as intimidation, sexual harassment, and misinformation aimed at discrediting their credibility and dignity. The study also highlights women’s resilience and resistance strategies. Documenting these experiences contributes to the development of more inclusive, adaptive, and responsive legal frameworks that ensure safe, meaningful political participation in digital spaces.